Socioeconomic disparities between oral cavity cancer patients in Germany - Muallah, David; Matschke, Jan; Muallah, Sophie; Klimova, Anna; Kroschwald, Lysann Michaela; Schröder, Tom Alexander; Lauer, Günter; Haim, Dominik (Frontiers in Public Health, 2022)
Objective In many countries the access to high quality medical service depends on socioeconomic factors. Therefore, these factors are associated with the treatment and prognosis of many diseases. In Germany health care is claimed to be independent from such factors due to obligatory health insurance and a well-developed medical infrastructure. Thus, socioeconomically caused health disparities should be absent. The aim of this study was to analyze the association between socioeconomic factors and the survival of oral cavity cancer in Germany. Patients and methods In this descriptive cohort study socioeconomic status related factors as well as demographic, tumor-specific, and comorbidity factors of 500 patients treated for oral cavity cancer were obtained in the university hospital of Dresden. Pearson correlation was used to describe associations between continuous variables. Associations between categorical variables were assessed using the chi-square test. Overall and recurrence-free survival were studied using the Kaplan-Meier method. Log-rank test was carried out to test between-group differences. Cox proportional hazard models were used to estimate the risk of death and the risk of recurrence. Results Significant differences in overall survival were found between the different educational levels and sex. Seventy-nine percent of the patients did not have a university degree or master craftsman/craftswoman. Less discrepancy was observed according to the marital status (49.4% married/engaged vs. 47.8% single, divorced, or widowed). In the multivariable analysis only sex, age at diagnosis, the Charlson score, the number of positive lymph nodes, and the nodal status were identified as independent predictors for overall survival whereas sex and the age at diagnosis were identified as independent predictors for recurrence-free survival. Conclusion Despite the equitable health system in Germany, significant associations between overall survival of oral cavity cancer and different socioeconomic factors could be found. For elimination of these disparities, health education programs should be established in socially deprived areas. Furthermore, clinicians should keep these factors in mind when determining recall periods for dental check-ups.